Knowledge, Attitude, and Practice of Thai Dairy Farmers on the Use of Antibiotics - Niorn Ratanapob; Aksorn Saengtienchai; Theera Rukkwamsuk (Veterinary Medicine International)
Antibiotics have been used regularly in dairy farms by veterinarians; however, they were also used occasionally by farmers without any veterinary prescriptions. Because knowledge, attitude, and practice are important for sustainable antibiotic use, the levels of these aspects among farmers and associated factors should be determined to improve antibiotic use in dairy farming. The study was carried out in 89 Thai dairy farmers, using a structured questionnaire. Data were analyzed using descriptive statistics. The questions were scored and the total scores were calculated for each aspect. Factors associated with knowledge, attitude, and practice scores were identified using the multivariate linear regression. The mean scores for knowledge, attitude, and practice were 62%, 86%, and 78%, respectively. Higher education, participation in a training related to antibiotic use, and being supervised by the Veterinary Teaching Hospital Nong Pho were associated with a higher knowledge score (p<0.050). Farmers with less experience received a higher attitude score (p=0.020). Acquiring antibiotic knowledge from other farmers was associated with a lower practice score (p=0.005). A positive association was found between knowledge and attitude scores (p=0.021) and practice and attitude score (p<0.001). Due to the insufficient knowledge on antibiotic use, there is a need to fill the gap to ensure prudent antibiotic use by farmers. Recommendations including training farmers by veterinarian to perceive the prudent antibiotic uses, encouraging young generation with higher education to participate in dairy farming, providing antibiotic use protocols, and decreasing the availability of antibiotics should be implemented to limit overuse by farmers.